Herd Behaviour, Short-Lived Phenomenon: Evidence from Pakistan Stock Exchange - Shaista Jabeen,; Sayyid Salman Rizavi (The Lahore Journal of Business)
This research intends to investigate the herd behaviour of investors in Pakistan Stock Exchange (PSX). Previous literature claims that herd behaviour is driven from fundamental information, which causes quick price adjustments to new information and thus leads to efficient markets. However, some researchers have claimed that herd behaviour does not depend upon fundamental information, and hence, leads to price instability. For the purpose of this research, the daily closing stock prices of 528 companies listed in the PSX have been used to calculate the stock returns. The market-wide herd measure, proposed by Chiang and Zheng (2010), has been used to compute the herd behaviour. The data has been investigated for autocorrelation, heteroscedasticity, and stationarity issues. Findings revealed that herding did not exist in PSX, but some sectors did follow this behaviour. This study can help regulators to comprehensively investigate market anomalies leading to smooth market processing